HUKUM KELUARGA ISLAM DALAM DINAMIKA SISTEM HUKUM DI INDONESIA - Aziz MK, Abdul (Irtifaq, 2014)
Study of Islamic family law inIndonesia and many Moslemcountries is very interesting andurgent because Islamic family lawdenotes a field of Islamic lawhas an important position. This isbecause of its contribution tobuild society regularly andhappily. Thus, many Moslemcountries including Indonesia havepay attention more to Islamic lawlegislation as positive law forinstance the Act o. 1 year 1974regarding the marriage law, theAct Nomor : 41 year 2004concerning the waqf, the Act Nomor: 7 year 1979 that has beenchanged by The Act Nomor 3 Year2006 about Religious Court. Theimpact of the positivization ofIslamic family law is there is thecertainty of Islamic law inIndonesia.